1999
DOI: 10.1051/aas:1999514
|View full text |Cite
|
Sign up to set email alerts
|

An AGN sample with high X-ray-to-optical flux ratio from RASS

Abstract: Abstract. We present the first results of a program to identify the unknown bright active galactic nuclei (AGN) in the ROSAT All Sky Survey Bright Source Catalog (RASS-BSC). We have used log C + 0.4 R as an alternative expression for log(f X /f opt ), where C is X-ray count rate and R stands for R magnitude. Then a high X-rayto-optical flux ratio criterion has been used to select an AGN sample with 165 unidentified X-ray sources for optical spectroscopy. Those 165 X-ray sources have been identified in the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 11 publications
3
15
0
Order By: Relevance
“…SHBL J013632.5+390559. This object has already been identified as BL Lac by Wei et al (1999). We confirm the identification, but its redshift cannot be determined because of the absence of emission and absorption features.…”
Section: Classificationsupporting
confidence: 70%
See 1 more Smart Citation
“…SHBL J013632.5+390559. This object has already been identified as BL Lac by Wei et al (1999). We confirm the identification, but its redshift cannot be determined because of the absence of emission and absorption features.…”
Section: Classificationsupporting
confidence: 70%
“…SHBL J075124.9+173051. This object was identified as Seyfert 2 by Wei et al (1999) with redshift z = 0.185. We confirm its redshift but classify it as BL Lac, as its optical spectrum does not show emission lines.…”
Section: Classificationmentioning
confidence: 99%
“…Flux F λ in units of 10 −16 erg/cm 2 /s/Å depending on the wavelength inÅ given in the observer rest frame. The spectra of #1 and #6 are obtained from Wei et al (1999), #2 is from Boroson & Green (1992) and the others are from Abolfathi et al (2018). and MMPP (Multi-Mode Photometer-Polarimeter) devices in photometric mode with 10 medium-band interference SED filters.…”
Section: Observational Technique and Reductionmentioning
confidence: 99%
“…The chosen attributes from different bands are B − R (optical index), B + 2.5log(CR), lgCR (source count-rate in the broad energy band), HR1 (hardness ratio 1), HR2 (hardness ratio 2), ext (source extent), extl (likelihood of source extent), J − H (infrared index), H − K (infrared index), J + 2.5log(CR). Wei et al (1999) chose logC0.4R + 4.9 as a criterion to preselect active galactic nucleus (AGN) samples, where C is the X-ray count rate and R is the R magnitude. According to the results of the Einstein Medium Sensitivity Survey (EMSS; Stocke et al 1991), the X-rayCtoCoptical flux ratio F X /F opt was found to be very different for different classes of X-ray emitters.…”
Section: Datamentioning
confidence: 99%